Anthropometric, physiological, and performance developments in cross-country skiers - Jones, T. W.; Lindblom, H.; Karlsson, Ø.; Andersson, E. P.; McGawley, K. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to describe changes in laboratory-assessed anthropometric and physiological characteristics, training volumes, and competitive performance in national development-team cross-country skiers over a 25-month period, and to analyze whether changes in competitive performance could be predicted by changes in laboratory-assessed qualities and training volumes. Methods: Data collected over 25 months from 30 national development-team cross-country skiers (14 women, 16 men; age, 18-23 yr) were analyzed retrospectively using multivariate statistics. Anthropometric and physiological characteristics were assessed via dual-energy x-ray absorptiometry and incremental roller-ski treadmill tests, respectively. Total training volumes and distributions of low- and high-intensity training were analyzed from online training diaries, and competitive performance was determined by International Ski Federation (FIS) distance and sprint points. Results: Whole- and upper-body lean mass increased in the full cohort of skiers (n = 30; both P < 0.05), whereas lower-body lean mass, whole-body fat mass, speed and oxygen uptake (V.O2) at a blood lactate concentration (BLa) of 2 and 4 mmol/L, as well as time-trial completion time, power output, and peak V.O2, improved in the women only (all P < 0.05). Valid predictive models were identified for female skiers` best FIS distance points (R2 = 0.81/Q2 = 0.51) and changes in FIS distance points (R2 = 0.83/Q2 = 0.54), with body mass, fat mass, lean mass, V.O2peak, and speed at a BLa of 4 mmol/L identified as consistently important variables for projection. Conclusions: The valid prediction of competitive performance was achieved for women only in distance events. This study suggests that improvements in body composition and aerobic capacity may be more beneficial for elite female development-level skiers than for their male counterparts. These results have implications for athlete selection and performance development.